The Emergency of Chronic Kidney Disease Patient in the Hospital Emergency’s Departement - Irna Mutmainnah; Raden Siti Jundiah; Vivop Marthi Lengga (GLOBAL HEALTH SCIENCE GROUP, 2025)
Chronic kidney disease (CKD) is a condition in which kidney function gradually declines. CKD has become a major global health issue due to its increasing prevalence each year. Emergencies in CKD patients include metabolic acidosis, hyperkalemia, pulmonary edema, and others. These conditions require immediate intervention to prevent organ damage or death. Objective: This study aims to describe cases of kidney disease emergencies in hospitals. Method: This study used a retrospective descriptive design. The sample size consists of 187 medical records of chronic kidney disease (CKD) patients. The sampling technique employed is Non-probability Sampling with a purposive sampling approach. The inclusion criteria are emergency department patient medical records with complete data, while the exclusion criteria are medical records from outside the year 2023. Data were collected using secondary data from CKD patient medical records in the Emergency Department. The analysis used univariate analysis with frequency distribution. Results: The majority of CKD patients experiencing emergencies were admitted to the emergency department (ED) with pulmonary edema. More than half of these patients were aged between 19-59 years, predominantly female, nearly half were housewives, and most had a history of hypertension. Almost all patients were undergoing hemodialysis therapy.Conclusions: This study shows that the most common emergency condition in chronic kidney disease (CKD) patients is pulmonary edema.